1996
DOI: 10.1002/(sici)1098-2795(199602)43:2<135::aid-mrd1>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activity and nucleolar ultrastructure of embryonic rabbit nuclei after transplantation to enucleated oocytes

Abstract: Changes in the level of transcriptional activity in 32‐cell stage morula nuclei were studied after blastomere electrofusion to enucleated oocytes. Nuclear transplant recipients were pulse labelled with 3H‐uridine during cultivation in vitro, embryos were then fixed and processed for autoradiography and electron microscopy. Transcriptional activity substantially decreased after 4.5 hr and was completely inhibited at last 15 hr after fusion. Transcription resumed thereafter in two‐cell stage embryos and could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…The fact that only NT with RCCs directly resulted in production of a cloned rabbit suggests that reprogramming occurs more easily with this type of cells. Surprisingly, acH3K9/14 signals of in vivo fertilized rabbit embryos were enhanced at the 4-cell stage but not at the 8-cell stage at which the rabbit embryonic genome activation occurs (Kanka et al 1996, Henrion et al 2000, Brunet-Simon et al 2001. However, initiation of mRNA synthesis determined by in situ hybridization with a poly (U) probe was first detectable at the late 2-cell stage (Kanka et al 1993) and autoradiographically detectable initiation of transcription from an embryonic rabbit genome occurs at the 4-cell stage (Christians et al 1994).…”
Section: In Vitro Developmentmentioning
confidence: 94%
“…The fact that only NT with RCCs directly resulted in production of a cloned rabbit suggests that reprogramming occurs more easily with this type of cells. Surprisingly, acH3K9/14 signals of in vivo fertilized rabbit embryos were enhanced at the 4-cell stage but not at the 8-cell stage at which the rabbit embryonic genome activation occurs (Kanka et al 1996, Henrion et al 2000, Brunet-Simon et al 2001. However, initiation of mRNA synthesis determined by in situ hybridization with a poly (U) probe was first detectable at the late 2-cell stage (Kanka et al 1993) and autoradiographically detectable initiation of transcription from an embryonic rabbit genome occurs at the 4-cell stage (Christians et al 1994).…”
Section: In Vitro Developmentmentioning
confidence: 94%
“…Of course, whether in mammals [17] and amphibians [18] , or in fishes [19] , this kind of ratio was terribly low. The previous studies in mammals indicated that most donor nuclei could be remodelled and transcriptionally suppressed to a certain degree under the circumstance of egg cytoplasm, and commonly turned on their transcriptional activity at the moment similar to the timing of ZGA [2,16,20,21] . However, the result in fish nuclear transplantation is quite different.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, similar experiments have been done to study the changes of transcriptional activity of donor nuclei. Kanka et al [2] found that the transcriptional activity of donor nucleus derived from 32-cell stage morula substantially decreased after 4.5 h and was completely inhibited at last 15 h after the nuclear transfer. The transcription resumed thereafter in 2-cell stage embryos and rapidly increased at 16-cell stage, reaching the transcriptional level typically as that of the 32-cell stage nuclei used for the transfer.…”
mentioning
confidence: 99%
“…Recently, Kanka et al [24] observed an excessive extrusion of pre-ribosomal particles in the cytoplasm at the 32-cell stage of rabbit embryos after nuclear transplantation. So far, it is necessary to continue this kind of work to clarify the role of rRNA during the early development in mammals.…”
Section: Discussionmentioning
confidence: 99%